Analysis of vegetation structure of urban parks and environmental discomfort index in The City of Mataram - Suripto Suripto; H. Ahyadi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The high population growth in Mataram City with the consequence of increasing development has caused a decrease in the area of ​​green open land. Garden parks as part of green open land need to be maintained and evaluated for their vegetation to be able to control the impact of local climate change. This study aims to analyze the vegetation structure of garden parks in Mataram City and assess its ability to reduce the increase in the environmental discomfort index. Vegetation analysis was carried out in six garden parks in Mataram City using the transect-squared method. The observed vegetation variable was the lushness of each vegetation life form. Vegetation data was analysed to produce groups of urban park vegetation structures in Mataram City. Microclimate factors inside and outside the park, which include air temperature and humidity observed on a sunny day according to a two-way line interval design with a direction according to the shape and area of ​​the observed urban park. The data of air temperature and humidity were processed to produce an index of environmental discomfort. The results showed that the six urban parks observed in The City of Mataram were divided into three groups of vegetation structures, namely the form of trees & shrubs (Ampenan Old Town Park, Udayana Garden and Selagalas park), forms of shrubs & trees (Sangkareang Park and Garden of Mayura ) and forms of bushes & shrubs (Malomba Park). The existence of city parks with variations in their vegetation structure in Mataram City does not cause variations in their ability to reduce the discomfort index. All city parks observed in Mataram City have moderate ability in reducing environmental discomfort index. Most of the areas outside the city parks in Mataram City have a class c of discomfort index and only Mayura Park, Malomba Park and Selagalas Park are known to reduce the discomfort class, namely from class c (discomfort felt by >50% of the population) outside the park to class b (discomfort felt by <50% of population) in the park.